Trends and patterns of analgesic utilization in Malaysia from 2010 to 2016: preference for tramadol - Zin, Che Suraya; Mohamed Nazar, Nor Ilyani; Ab Rahman, Norny Syafinaz; Alias, Nor Elina; Rani, Nurul Sahida; Ng, Kim Swan; Ye, Felicia Loh (Wiley, 2018)
Background: Inappropriate or irrational use of analgesics not only leads to increased morbidity and mortality rates and deterioration in quality of life, but can also give rise to misuse of health care resources and increase health care costs. Objectives: To evaluate the trends of analgesics prescribing at outpa- tient tertiary hospital settings and examine the patterns of their utili- zation in NSAIDs, tramadol, and opioid users. Methods: This cross‐sectional study was conducted from 2010‐2016 using the prescription databases of two tertiary hospitals in Malaysia. Prescriptions for nine NSAIDs (ketoprofen, diclofenac, celecoxib, etoricoxib, ibuprofen, indomethacin, meloxicam, mefenamic acid, and naproxen), tramadol and five other opioids (morphine, fentanyl, oxyco- done, dihydrocodeine, and buprenorphine) were included in this study.